2007
DOI: 10.1080/03601230701735078
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative buffers for fan emissions from poultry farms: 2. ammonia, dust and foliar nitrogen

Abstract: This study evaluated the potential of trees planted around commercial poultry farms to trap ammonia (NH 3 ) and dust or particulate matter (PM). Norway spruce, Spike hybrid poplar, hybrid willow, and Streamco purpleosier willow were planted on five commercial farms from 2003 to 2004. Plant foliage was sampled in front of the exhaust fans and at a control distance away from the fans on one turkey, two laying hen, and two broiler chicken farms between June and July 2006. Samples were analyzed for dry matter (DM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
(34 reference statements)
3
14
0
2
Order By: Relevance
“…The results confirm the short-range dispersion of N red emitted from a point source found in other works , but it may not be the same in other situations since it is dependent on the surrounding land-cover (e.g. trees vs. grass proportion) and on the number of animals in the barn (Adrizal et al, 2008;Verhagen and van Diggelen, 2006).…”
Section: Patterns Of Nitrogen Deposition and Atmospheric Ammoniasupporting
confidence: 79%
“…The results confirm the short-range dispersion of N red emitted from a point source found in other works , but it may not be the same in other situations since it is dependent on the surrounding land-cover (e.g. trees vs. grass proportion) and on the number of animals in the barn (Adrizal et al, 2008;Verhagen and van Diggelen, 2006).…”
Section: Patterns Of Nitrogen Deposition and Atmospheric Ammoniasupporting
confidence: 79%
“…This explains the higher vitality of the investigated species at site C at an increased distance (∼400 m) from the farm. This study confirms (<3 μg NH 3 m −3 ) what Tyndall and Colletti (2007) and Adrizal et al (2008) found with respect to the declining amounts of NH 3 from previously elevated levels at a relatively short distance from the farm. These authors proposed, therefore, the use of vegetative shelter belts, with modest heights (3-9 m), placed near agricultural sources in order to capture farm emissions.…”
Section: Relationship Between Atmospheric Nh 3 Concentration and Distsupporting
confidence: 91%
“…Various types of trees were able to play the role of a vegetative buffer by trapping aerial ammonia near poultry fans under different temperature conditions [27]. A follow-up study [28] further showed that different types of trees may effectively trap ammonia, particular matter (dust). Reduction in aerial ammonia depended on where plants were located in regards to distance to fans and type of tree (foliage).…”
Section: Discussionmentioning
confidence: 99%